Neurobehavioral plasticity in the rodent gustatory system induced by regular consumption of a low-calorie sweetener during adolescence - Clare M. Mathes; Sarah J. Terrill; Juan P. Taborda-Bejarano; Sandrine Chometton; Mallory J. Witt; Gaurikka Mendiratta; Emily G. Gilman; Delenn R. Hartswick; Bo M. Anderson; Lindsey A. Schier (Scientific Reports)
Abstract Habitual consumption of low-calorie sweeteners (LCS) during juvenile-adolescence can lead to greater sugar intake later in life. Here, we investigated if exposure to the LCS Acesulfame Potassium (Ace-K) during this critical period of development reprograms the taste system in a way that would alter hedonic responding for common dietary compounds. Results revealed that early-life LCS intake not only enhanced the avidity for a caloric sugar (fructose) when rats were in a state of caloric need, it increased acceptance of a bitterant (quinine) in Ace-K-exposed rats tested when middle-aged. These behavior shifts, which endured months after the end of Ace-K exposure, were accompanied by widespread changes in the peripheral taste system. The anterior tongue had fewer fungiform taste papillae, and the circumvallate papillae had a reduced anterior to posterior span and diminished expression of genes involved in sweet reception, sweet and bitter intracellular signaling, fructose transport, and cellular progeneration in the Ace-K-exposed rats. Ace-K exposure also led to a significant reduction in dopamine-producing cells of the ventral tegmental area. The collective findings reveal that LCS intake early in life alters the taste-brain axis and the behavioral responsiveness to both positive and negative tastants that are important determinants of dietary preferences.